Jerusalem unbound : geography, history, and the future of the Holy City - Dumper, Michael (Columbia University Press, 2014)
This history of Jerusalem examines its intersecting and multi-levelled matrix and, in so doing, portrays the constraints on Israeli control over the city and the resilience of Palestinian enclaves after 45 years of Israeli occupation. Adding to this complex mix is the role of numerous external religious, political, financial, and cultural influences, so that the city is also a crucible for broader contestation. The book concludes that the city will have to be shared and that the sharing will be based upon these many borders and the interplay between history, geography, and religion.